Co-governance Design and Implementation: Lessons from Norman v Tūpuna Maunga o Tāmaki Makaurau Authority - Houghton, Jayden (New Zealand Universities Law Review, 2024)
Norman v Tūpuna Maunga o Tāmaki Makaurau Authority is a judicial review of the Tūpuna Maunga o Tāmaki Makaurau Authority's decision to fell and remove all the exotic (non-native) trees on Ōwairaka/Mt Albert. Whilst the High Court dismissed the review and allowed the operation to proceed, that decision was overturned by the Court ofAppeal because the Maunga Authority failed to consult in accordance with statutory requirements. The Norman litigation has implications and lessons for all co-governance arrangements in Aotearoa New Zealand. This article argues that whilst the relevant Treaty of Waitangi settlement legislation allows for meaningful power-sharing within the Maunga Authority, and the co-governance partners sought to meaningfully share power, the Maunga Authority could have done more to consult and act in good faith. It also contends that tikanga Māori gives rise to a duty to consult and ought to be contemplated by counsel as a basis for a duty to consult in the future.
Keywords: Actions & defenses (Law); Courts; Judicial review; Trees

Whakapapa of a Prison Riot: Prison Censorship, Free Speech, and the Fight against Fascism - Rakete, Emmy; Lamusse, Ti (2024)
Starting with the whakapapa of the Waikeria Prison Uprising in 2020/21, this article examines what the suppression of prisoners’ freedom of speech tells us about the struggle to defeat the far right. Drawing on the authors’ personal experience of censorship at the hands of the Crown, the article demonstrates the futility of relying on the capitalist state to achieve the liberation of exploited and oppressed people. The article critiques liberal ‘safetyism’ as a demobilising force, which prioritises fear for personal safety over the necessity of struggle. In contrast, the authors argue that it is only through mass struggle that we can defeat the far right and liberate ourselves.

Indigenous climate justice in Aotearoa New Zealand: the dangers of (mis) recognition within climate policymaking - Parsons, Meg; Crease, Roa Petra (Inland Waters, 2024)

Rangatahi Maori climate action: A dialogue with nature-based solutions - Te One, Annie; Menzies, Diane; Pooley, Brittany; Logan-Riley, India (Nature-Based Solutions, 2024)
This article explores the broad area of rangatahi Māori climate activism. As a research team made up of academics, rangatahi and rangatahi Māori activists, this perspective piece discusses the importance of whakapapa, belonging and connections to the environment as a foreground to climate activism. While we highlight the lack of academic research focussed on rangatahi Māori climate activism, we show that there is a plethora of activity happening through digital and social media which provides a rich space for sharing innovative ideas for a just future in which nature is centered. We suggest that there are many commonalities between the current articulations of Nature-Based Solutions and rangatahi Māori activism and that greater dialogue between these spaces is vital for any solutions being offered for an environmentally just future for Aotearoa.
Keywords: Activism; Climate change; Digital media; Environment; Mātauranga; Rangatahi

Tikanga and New Zealand political parties—heading in the “right” direction? case study—2020 General Election - Te One, Annie; Caird, Clair (AlterNative, 2024)
This article examines references to tikanga Māori (Māori (the Indigenous Peoples of New Zealand) values) by New Zealand political parties. The article grounds itself in some of the wider debates relating to the incorporation and application of tikanga, Māori values, across New Zealand in both legal and political contexts, with particular review of legislative references. An analysis of New Zealand political party policies and constitutions from the 2020 General election showed that over half of the political parties who campaigned made some reference to tikanga, but there was great variation in how tikanga was interpreted. This article assesses some of the opportunities and complexities of New Zealand political party engagement with tikanga Māori.
Keywords: Election; Political Parties; Tikanga; Voting, Parties, Parliament

The Politics of Indigenous Exclusion in Australia and New Zealand - O’Sullivan, Dominic (Current History, 2024)
In both Australia and New Zealand, Indigenous peoples have called for alternative non-colonial political arrangements. In October 2023, Australians voted in a referendum against distinctive Indigenous participation in public policymaking, which had been proposed as a step toward a more inclusive political system. On the same day, New Zealand elected a new Parliament, leading to the formation of a government comprising three parties that had campaigned against what they saw as excessive Māori political influence. Comparing these developments and the histories of the two countries raises questions about liberal equality, democratic citizenship, and whether all or just some citizens should own the liberal democratic state.

Te Tiriti o Waitangi—neither “one people” nor partners: rangatiratanga and inclusive democratic kāwanatanga - O’Sullivan, Dominic (AlterNative: An International Journal of Indigenous Peoples, 2024)
Te Pati Māori (The Māori Party) proposes removing the British monarch as head of state so that Te Tiriti o Waitangi’s (the Māori text of the Treaty of Waitangi) (Te Tiriti) promise of fulfilling partnership may be realized. The ACT (Association of Consumers and Taxpayers) Party’s alternative argument is that partnership is among a body of treaty principles that give Māori people (Indigenous peoples of New Zealand) political advantage over others. These alternative perspectives transcend time because neither partnership nor equality as the ACT party presents it meets the possibilities of liberal democratic citizenship that may be read into Te Tiriti. Instead, equality is enhanced by interpreting Te Tiriti as constituting a commonwealth with hapū (sub-tribes) as existing political communities, and kāwanatanga (government) as a new one, with powers and responsibilities grounded in equal tikanga (cultural practices and proper conduct). The powers of government may then be shared, through participatory parity.

Region-level Pākehā warmth towards Māori enhances collective action intentions: An extension of the social identity model of collective action (SIMCA) - Houkamau, Carla; Bahamondes, Joaquín; Osborne, Danny; Sibley, Chris (International Journal of Intercultural Relations, 2024)
New Zealand is a peaceful nation, but ongoing political tensions and inequities between Māori (the indigenous peoples of New Zealand) and Pākehā (the majority group of Europeans) persist as a result of its colonial history. Identifying ways to redress the enduring legacy of colonialism are therefore of critical importance. Accordingly, this paper examines data from 7017 Māori, as well as 37,233 Pākehā, to examine the impact of regional-level Pākehā warmth towards Māori on Māori support for progressive collective action. Results reveal that Pākehā warmth towards Māori varies markedly across 257 regional wards (regional units created for New Zealand electoral purposes). Moreover, multilevel modelling demonstrates that Pākehā warmth towards Māori at the region-level correlates positively with Māori identity and political efficacy at the individual level which, in turn, both correlate positively with collective action support. Collectively, these results demonstrate the impact of the broader social climate on social change, while identifying a previously-unknown facilitator of collective action support (namely, a broader context of warmth towards structurally disadvantaged groups).
Keywords: Activism; Māori; Political rights; Social identity model of collective action (SIMCA)

Hauora hinengaro o takatāpui: analysing the effectiveness of mental health policies in addressing the needs of Takatāpui in Aotearoa New Zealand - Benvie-Watson, Emma; Greaves, Lara M. (Culture, Health & Sexuality, 2024)
Many studies have documented the effect that colonisation has had on takatāpui, that is, Māori (the Indigenous peoples of New Zealand) with diverse gender identities, sex characteristics and sexualities. In this paper, we explore whether current Aotearoa New Zealand (hereafter Aotearoa) mental health policies meet the needs of takatāpui. We identified five mental health policy needs, informed by the literature. We then explored policy documents from government ministries, district health boards and non-government organisations to see the extent to which policy met these needs. Four themes were present in the literature analysed: an overall lack of acknowledgment of takatāpui and intersectionality; promising engagement with the needs of takatāpui by NGOs; symbolic commitment to Te Tiriti o Waitangi; and some limited engagement with Māori health models. The findings show promise in some areas but demonstrate a lack of engagement by policy to meet the needs of takatāpui.
Keywords: Identity & Intersectionality; Mental health; Māori; Policy; Takatāpui